STORE, ATMOSPHERE,DI, CAFÉ, MIE, API, NARAKO, PADANG - Pratama, Fadel Ferza (RC-INSTITUT, 2019)
This study aims to describe store atmosphere at Mie Api Narako Padang Café in terms of store layouts exterior indicators and interior displays. This research is descriptive quantitative using the survey method. The population in this study were consumers who had already made a purchase at Narako Mie Api Cafe Padang. The sampling technique is purposive sampling, so based on the calculation the number of samples is 97 people. The results of the description of the research data show the following: 1) exterior shows the highest percentage score which is equal to 40.2% in the sufficient category; 2) the interior shows the highest percentage score which is equal to 35.1% in the good category; 3) store layout shows the highest percentage score that is equal to 40.2% in the sufficient category; and 4) the interior displays show the highest percentage score of 47.4% in the sufficient category